THE BLACK AND THE CASPIAN: RUSSIA’S WARM SEAS - TCHANTOURIDZE, Lasha (CENTRAL ASIA AND THE CAUCASUS, 2018)
By defeating Georgia and Ukraine in small wars, Russia has managed to consolidate its military dominance over the Black Sea and has halted NATO’s eastward ambitions. Faced with Moscow’s willingness to use naked aggression and military force, the United States and its Western allies have been unable to do anything to stop and reverse Russia’s territorial gains in the former Soviet Union or to counter its growing influence beyond. Soon after the collapse of the Soviet Union, Russia’s position in the Black Sea region appeared to be weakening, but its dominant status was once again recovered in the first decade of the 21st century. Moscow has subsequently used its controlling position in the Black Sea for a successful military campaign in Syria, where the Russian forces have aided the Syrian regime in its fight against the Islamic radicals and other opposition forces. In this Middle Eastern engagement, Russia has demonstrated its newly found advantage in strategic force deployment, in which the Caspian Sea Flotilla played a surprising and effective role. Unlike the Black Sea, the Caspian Sea has seldom figured in anyone’s strategic calculations beyond its immediate littoral states, but as Russia’s Caspian Sea Flotilla has made it evident, now this landlocked sea holds an important position in Russia’s overall military posture. Although the United States has managed to throw cold water on Russia’s enthusiasm in demonstrating new strategic weapons systems, Washington can do nothing to stunt Moscow’s advances on the ground in Syria and elsewhere. As a result, for the first time since World War II, Russia’s influence and power in the Middle East exceeds that of the United States or of any other major power. Russia’s continuing military presence and control over its two warm seas, the Black and the Caspian, has been crucial in expanding Moscow’s influence beyond Russia’s immediate neighborhood, with the Middle East occupying a prominent place in Moscow’s new international political and military calculations.